Project-Based Learning Implementation in Improving X Grade Student Colaborative Skills of Computer Network Enginering - Murniati, Murniati; Lamada, Mustari; Firdaus, Firdaus (Jurusan Pendidikan Teknik Elektro, 2025)
This study aims to determine the results and effects of the implementation of project-based learning on the collaborative abilities of class X students majoring in Computer Network Engineering at SMK 3 Enrekang. This study is a classroom action research conducted in two cycles. Each cycle consists of four stages including the planning stage, implementation stage, observation stage, and reflection stage. The subjects in this study were 19 class X TKJ students. The data collection techniques used were observation, questionnaires, and documentation. Based on the results, it showed an increase in the implementation of learning from 74% in cycle I to 91.46% in cycle II, with a difference in increase of 17.46%. Collaborative abilities also increased, with an average observation from 54.04% to 72.81% with a difference in increase of 18.77%, and a questionnaire from 55.20% to 91.46% with a difference in increase of 36.26%. The results of this study indicate that the project-based learning model is effective in improving student collaboration